A study on the impact of distance between tranducer and objects affecting efficiency of ultrasonic cleaning machine - Nguyen, Ngọc Phương; Nguyen, Xuân Quang (Journal of Technical Education Science, 2011)
Nowadays the cleaning devices play an important role in manufacturing industry, health care as well as domestic works… The classical cleaning methods combining manual and chemical substances are not appropriate for objects with complex shapes. Using ultrasonic wave is a good way to solve the above problems. It can meet the cleaning requirements such as technology, efficiency, high-speed… which other methods cannot. The main factors affecting the result of performance of washing machines are ultrasonic waves, heat, chemicals, and time. This paper illustrates how the arrangement of vibrators and the distance between objects and vibrating sources affect the efficiency of ultrasonic washing machines. The research will give the best arrangement of objects in washing machines to optimize their performance.